A biological perspective for the fishery management of a small urban lake in Indonesia: a case study on the reproductive stage of the red devil (Amphilopus citrinellus) in Situ Cilodong, West Java, Indonesia - Ira Akhdiana; Rahmi Dina; Gema Wahyudewantoro; Fajar Sumi Lestari; Eva Nafisyah; Dian Oktaviyani; Agus Waluyo (BRIN Publishing, 2023)
The presence and establishment of invasive alien fish species is one of the biggest threats to aquatic biodiversity. The red devil, Amphilopus citrinellus, is one of the emerging invasive species and its occurrence is massively detected in common water bodies in tropical areas such as Indonesia. However, the topic remains under-reported from the small urban lakes. This study aims to present the reproductive characteristics of the fish in Situ Cilodong, a small urban lake in the country, that can be used as a principal reference for population control. The sampling was conducted in June 2021 and May 2022 using a mix of seven mesh-sized gillnets. The results of the length-weight relationship reveal that both the female and male fish perform isometric growth type. The calculated Gonad Somatic Index (GSI) and the histological analysis confirmed that the fish is a multi-spawner species. The results imply that sustainable population control efforts must include intensive catch and engage a participatory approach between the legal authority and the local fishers.